Extrusion parameter optimization to improve the mechanical performance of recycled PLA-PETG blends using Taguchi-GRA approach - Annisa Fatimatus Zahro; Ihwan Ghazali; Achmad Pratama Rifai; Wangi Pandan Sari (Universitas Mercu Buana, 2026)
Recycled polymers offer a promising pathway toward sustainable additive manufacturing, but their mechanical performance is often limited by degradation and incompatibility between mixed materials. This study investigates the optimization of extrusion parameters for recycled PLA–PETG blends to improve tensile strength and ductility. The Taguchi method was applied to efficiently evaluate the effects of PLA content, temperature, and extrusion speed, while Grey Relational Analysis (GRA) was incorporated to enable simultaneous optimization of tensile strength and elongation, which cannot be achieved using Taguchi alone. The Taguchi–GRA approach identified 30 wt% PLA, 225 °C, and 300 mm/min as the optimal parameter set, producing filament with a tensile strength of 7.47 MPa and elongation of 1.58%, corresponding to a 28% improvement over the lowest-performing condition. Although the optimized recycled filament exhibited significantly lower properties than commercial PETG, the performance is adequate for low-stress functional applications such as prototyping components and non-load-bearing parts. Fractographic analysis further revealed poor interlayer and interfacial adhesion, explaining the limited ductility of the recycled blends. These findings demonstrate that combining Taguchi and GRA provides a practical route for balancing strength and ductility in sustainable filament development and provides a foundation for future improvements through the use of compatibilizers, post-processing, and enhanced extrusion control.